Association of HFE gene mutations with nonalcoholic fatty liver disease in the Iranian population - Saremi, L.; Lotfipanah, S.; Mohammadi, M.; Hosseinzadeh, H.; Sayad, A.; Saltanatpour, Z. (Cellular and Molecular Biology, 2016)
To determine whether the HFE gene variants H63D and C282Y are associated with NAFLD in persons with type 2 diabetes, we conducted a case-control study including 145 case of NAFLD patients with a history of type 2 diabetes and 145 matching control. The genomic DNA was extracted from the peripheral venous blood and the genotyping of HFE gene mutations was analyzed using the PCR–RFLP technique. Statistical analysis was performed using SPSS 12.0 software by Ï‡2 test, t test and ANOVA (P<0.05). Data showed no increased frequency of HFE mutations in persons with type 2 diabetes and no association between H63D mutation and NAFLD in the study population. Also, we analyzed index of physiological variables including FBS, lipid profile (TC, TG, LDL-C, and HDL-C), BMI, HbA1c, and micro albuminuria and Cr levels). Data showed there are no relationship between these indexes and HFE gene mutations and either NAFLD as a complication of diabetes. But our results showed a relationship between C282Y mutation and NAFLD in persons with type 2 diabetes. C282Y mutation might be a genetic marker of NAFLD in Iranian population.